Recent advancement of anti-resonant hollow-core fibers for sensing applications - Ni, Wenjun (2021)
Specialty fibers have enabled a wide range of sensing applications. Particularly, with the recent advancement of anti-resonant effects, specialty fibers with hollow structures offer a unique sensing platform to achieve highly accurate and ultra-compact fiber optic sensors with large measurement ranges. This review presents an overview of recent progress in anti-resonant hollow-core fibers for sensing applications. Both regular and irregular-shaped fibers and their performance in various sensing scenarios are summarized. Finally, the challenges and possible solutions are briefly presented with some perspectives toward the future development of anti-resonant hollow-core fibers for advanced sensing.